Panic postponed. (Economist, 2000)
Discusses the year 2000 (Y2K) date conversion scare and questions whether the United States overspent on preparing for trouble. Other countries which spent very little time and money and had no problems; How countries and businesses that began preparing late were able to obtain information from companies which were already compliant.